2012
DOI: 10.7448/ias.15.6.18106
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis in HIV‐infected patients: predictors for serological failure and serofast state

Abstract: PurposeHIV-infected patients treated for syphilis may be at increased risk for serological failure and serofast state. Our aim was to analyse serological response to treatment in HIV-infected patients diagnosed with syphilis, and factors associated with serological cure and serofast state.MethodsOpen-label, no controlled study of a series of HIV-patients diagnosed with syphilis during 2004–2011. Patients were categorized by rapid plasma reagin titer (RPR) into success (4-fold decrease in RPR by 12 or 24 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The immune status of serofast patients is unclear. A recent study reported that HIV-infected patients are at increased risk for serofast state after treatment [54]. Our results showed that these patients had enhanced circulating Treg numbers and suppressive function, also suggesting serofast status may be associated with a systemic immune suppression.…”
Section: Discussionsupporting
confidence: 69%
“…The immune status of serofast patients is unclear. A recent study reported that HIV-infected patients are at increased risk for serofast state after treatment [54]. Our results showed that these patients had enhanced circulating Treg numbers and suppressive function, also suggesting serofast status may be associated with a systemic immune suppression.…”
Section: Discussionsupporting
confidence: 69%
“…Some studies suggest that immunological status can influence serological response to syphilis treatment in HIVinfected patients. 16,17 We could not confirm these findings as the number of CD4 cells was not a significant modifier of serological response to penicillin treatment. However, our sample was too small.…”
Section: Discussionmentioning
confidence: 79%
“… 9 Among 104 early syphilis and 36 late or indeterminate latent syphilis cases in a Malaga study from 2004 to 2011, 65 of 85 (76.4%) with prior known HIV-1 infection were taking HAART. 10 A retrospective, descriptive study at the University of Alabama found 40 incident syphilis cases from 2004 to 2007 in 1544 patients who were HIV-1 positive. 11 Two-thirds were receiving HAART when syphilis was diagnosed including all five patients with primary syphilis.…”
Section: Resultsmentioning
confidence: 99%